Nasal vestibular body treatment for recalcitrant nasal obstruction. Issue 3 (3rd February 2020) - Ibrahim, Nour; Tyler, Matthew A.; Borchard, Nicole A.; Rathor, Aakanksha; Nayak, Jayakar V.
Abstract : Background: The nasal vestibular body (NVB) is a recently reported dynamic swell body present in the inferolateral internal nasal valve. The contribution of NVB presence to persistent nasal obstruction, and effects of NVB treatment, are undefined. Methods: Thirty‐five patients with recalcitrant nasal obstruction and NVB presence were retrospectively reviewed between 2013 and 2019, including 25 patients (48 sides) who had NVBs reduced via radiofrequency ablation (RFA) and 10 patients (20 sides) who had untreated NVBs. Posttreatment healing and complications were reviewed at early (<1 month) and late (mean, 7.3 months) time‐points after RFA of the NVB. A subset of the NVB‐treatment patients (18 of 25 patients) were compared with 10 NVB‐control patients for pre‐/posttreatment outcomes using 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and subdomain scoring. Results: NVBs were successfully reduced in 100% of cases (48 of 48 sides) over both time‐points. Early sequelae of NVB treatment, such as local crusting (22 of 23, 95.6%) and bone exposure (4 of 23, 17.3%), resolved by the late time‐point, with complete remucosalization (23 of 23, 100%) of all NVB treatment sites. No persistent pain, sensory loss, or pyriform aperture stenosis was noted from any patient/side. Significant reductions between mean pre‐ and postoperative SNOT‐22 (−24, p = 0.001) and individual subdomain (−2, p = 002) scores were seen in the NVB‐treatment patients compared to the reductions in NVB‐controls (−8 and −1, respectively, both p > 0.001). Conclusion: NVB treatment using RFA is safe and highly effective, providing complete swell body reduction with only transient local morbidity. NVB presence contributes to persistent/recalcitrant nasal obstruction, with significant improvement in nasal airway function noted after NVB soft tissue reduction.